Glycerin and essential oils in the diet of Nellore bulls finished in feedlot: animal performance and apparent digestibility - Silva, Lorrayny Galoro da; Torrecilhas, Juliana Akamine; Ornaghi, Mariana Garcia; Eiras, Carlos Emanuel; Prado, Rodolpho Martin do; Prado, Ivanor Nunes do (Acta Scientiarum. Animal Sciences, 2014)
Current research studied the effect of partial replacing corn by glycerin and essential oils addition in the diet of Nellorebulls finished in feedlot. Thirty bulls with average weight 400 ± 34.1 kgwere housed in collective pens (10 x 20 m2) for 63 days. The bulls were randomly assigned to 3 diets (10 bulls per treatment): CON – Control (without glycerin or Essential® oils); GLY – Glycerin (15% on dry matter - DM); and GEO – Glycerin (15% on DM) and Essential® oils (3 g animal day-1). Three different markers were used to estimate apparent digestibility in the diets: indigestible dry matter –iDM; indigestible neutral detergent fiber – iNDF; and purified lignin – LIPE®. Feed efficiency and animal performance were not affected by the corn partial replacing by glycerin. Partial corn replacing by glycerin and Essential® oils addition in the diets increased the DM and organic matter apparent digestibility for bulls. The glycerin addition in the diet decreased NDF, fibrous carbohydrate and non-fibrous carbohydrate digestibility. Apparent digestibility estimated by markers iDM, iNDF and LIPE® were similar to all nutrients in the diet.